Caulim e sua interação com inseticidas no controle de Dalbulus maidis (Delong & Wolcott) (hemiptera: cicadellidae) e nos aspectos agronômicos do milho - Finotti, Camila Garcia Dutra (2024)
The use of kaolin spraying is a promising alternative for the management of many agricultural pests. The spray of kaolin creates a film of fine particles on the surface of the leaves that can protect the plant from heat stress, promote the death of insects through desiccation, interfere in the selection process of the host plant by the insect pest and promote increases in productivity. The aim of this study was to evaluate the use of kaolin, associated or not with insecticides, in the control of Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) and in the agronomic aspects of maize. To this end, two experiments were set up under field conditions, one in the second season 2023 and the other in the first season 2023/2024. The experimental design was randomized blocks with four replications and the commercial product Surround® WP was used as the kaolin source. In the second season trial, three applications were made (V4, V6 and V8). The treatments were: 1 - control, 2 - foliar insecticide, 3 - foliar insecticide and Surround® WP (7,5kg/ha), 4 - foliar insecticide and Surround® WP (3 kg/ha) and 5 - Surround® WP (2 kg/ha). The active ingredients of the insecticides used were Imidacloprid + Bifenthrin in the first application, Dinotefuram + Lambda-cyhalothrin in the second application and Imidacloprid + Beta-cyfluthrin in the third application. In the first season trial, two applications were made (V6 and V8) and the treatments were: 1 - control, 2 - foliar insecticide, 3 - foliar insecticide and Surround® WP (7,5kg/ha), 4 - foliar insecticide and Surround® WP (3kg/ha), 5 - Surround® WP (2kg/ha) and 6 - Surround® WP (3 kg/ha). The active ingredients of the insecticides used were Isocicloseram + Lambda-cyhalothrin, in the first application and Chlorfenapyr and Isocicloseram in a mixture of syrup in the second application. The application of kaolin alone did not reduce the leafhopper population when compared to the control, neither in the second nor in the first season. In the second season, there was no difference in the average number of leafhoppers or in the efficacy of any of the products tested. In the first season, at six days after the first application, the application of kaolin alone was less effective than when the insecticide was applied, while one day after the second application, there was a reduction in the leafhopper population compared to the control and greater effectiveness when the insecticides or kaolin were applied together with the insecticides. None of the products tested reduced the symptoms of the blight complex or affected the height of insertion of the first ear, the height of insertion of the floral pendant or the diameter of the corn stalk in the second season. The foliar application of kaolin increased the weight of the corn ear, more strongly in the second season and at the lowest doses tested (2 and 3 Kg/ha). Although it did not reduce the population of D. maidis or the symptoms of blight alone or in combination with insecticides, the use of kaolin was promising for increasing maize productivity, especially in plants with greater biotic and abiotic stress pressure in the second season.